2016
DOI: 10.1136/bmjdrc-2016-000216
|View full text |Cite
|
Sign up to set email alerts
|

PERS&O (PERsistent Sitagliptin treatment & Outcomes): observational retrospective study on cardiovascular risk evolution in patients with type 2 diabetes on persistent sitagliptin treatment

Abstract: ObjectivesThe UK Prospective Diabetes Study (UKPDS) Risk Engine (RE) provides the best risk estimates available for people with type 2 diabetes (T2D), so it was applied to patients on persistent sitagliptin treatment.DesignA ‘real-world’ retrospective, observational, single-center study.SettingThe study was performed in a general hospital in Northern Italy in order: (1) to validate UKPDS RE in a cohort of Italian participants with T2D without prespecified diabetes duration, with/without cardiovascular (CV) dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The UK Prospective Diabetes Study Risk Engine has been used in an observational retrospective study in 170 patients with type 2 diabetes in Italy on sitagliptin to evaluate cardiovascular risk evolution and found analysis of variance testing showed a significant effect on increased CV risk at 12 months ( P = 0.003) and 48 months ( P = 0.04) …”
Section: Hierarchy Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The UK Prospective Diabetes Study Risk Engine has been used in an observational retrospective study in 170 patients with type 2 diabetes in Italy on sitagliptin to evaluate cardiovascular risk evolution and found analysis of variance testing showed a significant effect on increased CV risk at 12 months ( P = 0.003) and 48 months ( P = 0.04) …”
Section: Hierarchy Of Evidencementioning
confidence: 99%
“…53 The findings of these massive observational studies of real world data provides some reassurance regarding this serious outcome, despite the conflicting results from RCTs for DPP-IV inhibitors.. [28][29][30]54 The UK Prospective Diabetes Study Risk Engine has been used in an observational retrospective study in 170 patients with type 2 diabetes in Italy on sitagliptin to evaluate cardiovascular risk evolution and found analysis of variance testing showed a significant effect on increased CV risk at 12 months (P = 0.003) and 48 months (P = 0.04). 55 An observational propensity score-matched study of 414 213 participants aged 65 years or more identified from the National…”
Section: Safetymentioning
confidence: 99%
“…The findings of several RWE trials support the effectiveness of dulaglutide, but to our knowledge only two of these were prospective studies [ 14 , 15 ], both of which have a number of limitations, such as short duration (3–6 months) and a limited number of cases (< 200). The centers which participated in the present study have some experience in collecting real-life retrospective data [ 16 ], and both the European Medicines Agency and the US Food and Drug Administration have approved the use of RWE to integrate data from RCTs for regulatory decisions [ 17 19 ]. We became interested in conducting an independent prospective real-world observational study [ 15 ] on the clinical utilization of dulaglutide shortly after it became available clinical use in Italy in 2016, involving 16 different centers in Lombardy region.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The present study (PERS&O 2.0) is a long-term real-world retrospective, observational, single-center, longitudinal study performed in a general hospital in Northern Italy. 1 We collected data about 440 patients with T2D prescribed sitagliptin in accordance with the Italian Pharmacological Agency (AIFA), meaning that some limitations (in terms of HbA1c values and possible drug association) were present. Nevertheless, the most important thing was to obtain a better glycemic control (stated by HbA1c evolution), independently of diabetes duration, body weight, previous CV disease.…”
Section: Discussionmentioning
confidence: 99%
“…The PERsistent Sitagliptin treatment & Outcomes (PERS&O) study 1 was a ‘real-world’ retrospective, observational, single-center study performed in a general hospital in Northern Italy in order…”
Section: Introductionmentioning
confidence: 99%